Decoding Stocks Patterns Using LSTM - Dr. Madhur Jain,; Shilpi Jain,; Ankit Gupta, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Decoding stocks is extensively utilized in the financial sector by numerous organizations. It is volatile in nature, so it’s tough to predict the prices of stock. Numerous methodologies exist for tackling this task, including logistic regression, support vector machines (SVM), autoregressive conditional heteroskedasticity (ARCH) models, recurrent neural network (RNN), convolutional neural networks (CNN), backpropagation, Naïve Bayes, among others. Among these, Long Short-Term Memory (LSTM) stands out as particularly adept at handling time series data. The primary aim is to discern prevailing market trends and achieve accurate stock price forecasts. Leveraging LSTM and RNN , we strive for error free stock price predictions, with promising results.
Keywords: Stock market; ML; DL; LSTM; CNN; Trade